226Ra/238U and 228Th/228Ra disequilibrium as weathering indices in beach sand sediments associated with granitoids from Cyclades. Greece. (January 2019) - Papadopoulos, A.
Abstract: Radioactive secular disequilibrium measured as the absolute difference from 1 of the 226 Ra/ 238 U and 228 Ra/ 228 Th ratios have been used to determine weathering extent. Twenty-eight samples from beach sands of Cyclades islands, all of them being the weathering products of the local granitic plutons, are studied for their secular disequilibrium in both 238 U and 232 Th series ( 226 Ra/ 238 U and 228 Th/ 228 Ra respectively). The results are compared to weathering indices already in use worldwide and suggest a significant linear correlation of U-series disequilibrium with WIP (alkaline and alkaline-earth element leaching) and PWI (silica leaching) for the beach sands studied and significant non-linear correlations with CIA (chemical index of alteration) and PIA (plagioclase index of alteration). Considering only the heavy mineral enriched samples, significant correlations exist between U-series disequilibrium and CIA, CIW (chemical index of weathering) and PIA. Therefore, with an appropriate choice of the weathering index and samples both U-series and weathering index can recover the extent of chemical weathering. On the other hand, the use of Th-series disequilibrium as a weathering index is limited, due to 228 Th and 228 Ra geochemistry and especially due to their short radionuclide half-lives. U-series disequilibrium can therefore be used as a relatively sensitive weathering index in sediments consistent with CIA, CIW and PIA indices. However, the mineralogical composition must be considered. More specifically the mineral content of the sediments should involve considerable amounts of sensitive to weathering minerals (e.g. Fe-Mg minerals) as well as feldspars. Highlights: The use of Th-series disequilibrium as a weathering index is limited. U-series disequilibrium be used as a sensitive weathering index in sediments. High amounts of sensitive to weathering minerals are necessary for best results.